Effect of chemical modification of grafts on the survival improvement post haploidentical bone marrow transplantation in mice - Yang, Guang (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2004)
OBJECTIVE: Human leukocyte antigen (HLA) haploidentical bone marrow is a potential source of donor to children for its availability. The drawback is deleterious graft versus host disease (GVHD) reaction post transplantation because of the incompatibility of HLA antigen expression between donors and recipients, in which donor T lymphocyte is stimulated to proliferate and differentiate. The methoxy polyethylene glycol (mPEG) is a kind of amphoteric compound without immunogenicity, which was used to modify various proteins covalently and to prepare the versatile blood type. If mPEG modification blocks the activation of T cells in grafts, GVHD reaction probably would become less serious and transplantation might become successful. The aim of this study was to verify the improvement of haploidentical bone marrow transplantation (BMT) in a murine model by using mPEG of certain concentration to modify the grafts